2010
DOI: 10.1042/bj20100016
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E inhibits Toll-like receptor (TLR)-3- and TLR-4-mediated macrophage activation through distinct mechanisms

Abstract: Synopsis Previous studies showed that apolipoprotein E (apoE) expression in macrophages suppresses inflammatory response. Whether the endogenously synthesized apoE acts intracellularly or after its secretion in suppressing macrophage inflammation remains unclear. The current study used the murine macrophage cell line RAW 264.7 to examine the influence of exogenous apoE on macrophage inflammatory responses induced by toll-like receptor (TLR)-4 and TLR-3 agonists lipopolysaccharide (LPS) and poly(I-C), respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 51 publications
0
36
1
1
Order By: Relevance
“…It should be noted that the difference in infl ammatory phenotype we have measured in adipose tissue from control and SEKO mice may be related to the reduced apoE expression in either macrophages or adipocytes. Others have shown that exogenously added apoE can modulate macrophage infl ammatory state but, interestingly, suppresses the infl ammatory phenotype ( 37,38 ). Our results, however, imply that the expression of apoE in adipose tissue promotes an infl ammatory phenotype.…”
Section: Discussioncontrasting
confidence: 55%
“…It should be noted that the difference in infl ammatory phenotype we have measured in adipose tissue from control and SEKO mice may be related to the reduced apoE expression in either macrophages or adipocytes. Others have shown that exogenously added apoE can modulate macrophage infl ammatory state but, interestingly, suppresses the infl ammatory phenotype ( 37,38 ). Our results, however, imply that the expression of apoE in adipose tissue promotes an infl ammatory phenotype.…”
Section: Discussioncontrasting
confidence: 55%
“…Previous studies have shown that apoE3 may protect against metabolic diseases via its anti-oxidation and anti-inflammatory properties (2,6), including its attenuation of toll-like receptor signaling and converting the pro-inflammatory M1 macrophages to the anti-inflammatory M2 macrophage phenotype (7,8). In the vessel wall, apoE3 also induces anti-inflammatory signaling events that limit injury-induced neointimal hyperplasia and hypercholesterolemia-induced atherosclerosis (9 -13).…”
mentioning
confidence: 99%
“…For example, apoE produced by macrophages relieves the inhibition of eNOS by caveolin in endothelial cells by displacing the caveolin from its complex with the NO synthase (87). Exogenous apoE inhibits macrophage activation by TLR3 and TLR4 agonists through distinct mechanisms (88). There is also an effect of apoE on arterial smooth muscle cells that is most clearly demonstrated in the increased formation of neointimal expansion in Apoe / mice in response to endothelial denudation (89).…”
Section: Coronary Atherosclerosis and Myocardial Infarction Inmentioning
confidence: 84%